2018
DOI: 10.3389/fpsyg.2018.01800
|View full text |Cite|
|
Sign up to set email alerts
|

Digital Storytelling in Early Childhood: Student Illustrations Shaping Social Interactions

Abstract: This study tests an instructional model designed to empower students in an early childhood classroom as emerging digital storytellers. Educators can use digital storytelling to support students’ learning by encouraging them to organize and express their ideas and knowledge in an individual and meaningful way while developing voice and facility in child–computer interactions. This work also helps develop traditional communication skills, fosters collaboration, and strengthens emergent literacy practices. Studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Based on the results of a needs analysis conducted by observing learning and questionnaires to Sunday school teachers, it was found that the majority of teachers still mostly use the storytelling method in teaching. Storytelling techniques that are done traditionally and with digital learning can develop communication skills, collaboration, and strengthen children's literacy practices (O'Byrne et al, 2018). In addition, storytelling can also increase learning motivation (Lee, 2012) and children's language skills and language abilities (Mokhtar et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of a needs analysis conducted by observing learning and questionnaires to Sunday school teachers, it was found that the majority of teachers still mostly use the storytelling method in teaching. Storytelling techniques that are done traditionally and with digital learning can develop communication skills, collaboration, and strengthen children's literacy practices (O'Byrne et al, 2018). In addition, storytelling can also increase learning motivation (Lee, 2012) and children's language skills and language abilities (Mokhtar et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The second factor, "contributions to the development of academic and socio-affective competencies" refers to the contributions of the digital stories related to the development of competencies linked to academic development, such as the development of oral and written language, the improvement of oral expression and communication, as well as the promoting of the acquisition of competencies related to the process of socialization of the individuals and the development of greater affectivity. These contributions have been evaluated and included in previous studies by previous researchers [17][18][19]. These studies have pointed out how the training in the use of these digital tools, such as the case of digital stories, contributes to the acquisition of competencies of the teachers-in-training, and how this also affects the students that these teachers will teach in the stages of early childhood education and primary education [20,46].…”
Section: Discussionmentioning
confidence: 99%
“…These studies referenced the advantages of digital stories [14][15][16], such as the improvement in academic, social and communication skills, imagination, creativity, critical thinking, expression, etc. [17][18][19]. Also, they help in the development of skills from the design, creation, and publishing of content, promoting collaborative and cooperative learning, which provides numerous benefits to teamwork: Initiative, responsibility, equality of opportunities, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning to write in multi-modal environments can also be a benefit. According to Mayer (2007), when children learned to write with different materials or on different surfaces, it helped to build fine motor skills and motivated them to write.…”
Section: Introductionmentioning
confidence: 99%